EFEKTIVITAS MEDIA CARD MATCH TERHADAP KEMAMPUAN PENGUASAAN KOSAKATA BENDA (MOCHIMONO) DAN (KYOUSHITSU NO NAKA) SISWA KELAS X SMA NEGERI 17 SURABAYA TAHUN AJARAN 2017/2018 - SYIFA, QOYIMATUS (HIKARI, 2018)
This study examines the mastery of vocabulary in Japanese language class X MIA 4 students of SMA Negeri 17 Surabaya. Based on the results of pre-research interviews with Japanese subject teachers, in the learning process in the classroom it can be seen that students still experience difficulties in memorizing and understanding the vocabulary of objects (meishi). Therefore, the use of Card Match media to overcome students difficulties in memorizing and understanding the vocabulary of objects (meishi). Media Card Match is a card media that each vocabulary consists of 3 cards containing hiragana, how to read (yomikata) and meaning (imi). The way to play it is to match cards that contain hiragana, how to read (yomikata) and meaning (imi) then paste it in a media. This study aims to determine the effectiveness of Card Match media on the ability of object vocabulary mastery (meishi) and student response to Card Match media in the ability of vocabulary mastery objects (meishi) in class X MIA 4 Surabaya State 17 High School. Media Card Match has been validated to media experts.This research is an experimental research using a quantitative approach and included in the Quasi Experimental Design research which was held on April 23-25 2018. The population of this study were students of class X MIA SMA Negeri 17 Surabaya with a sample of class X MIA 4 as an experimental class of 34 students. Based on the results of the experimental class pre-test and post-test sheets it is known that Card Match media is effectively used or has a positive influence on the experimental class. This is because the Media Card Match can facilitate students in mastering the vocabulary of objects (meishi). Besides the results of the t-significance calculation, the results obtained are 9.99. This value is greater than the t table value of 2.49. So it was concluded that Card Match media had a significant effect on the ability of object vocabulary mastery (meishi) of class X students of SMA Negeri 17 Surabaya in the academic year 2017/2018.Based on student questionnaire data analysis that shows strong criteria, as many as 93.38% said that learning vocabulary objects (meishi) using Card Match media is very interesting and fun and can create an atmosphere of active learning, as many as 88.97% said that the use of Card Match media could increase my learning motivation in learning Japanese vocabulary, as many as 91.17% said that the use of Match Media Cards could facilitate me in learning Japanese vocabulary, as many as 90.44% said that the use of Card Match media can train collaboration with groups, 93.38% said that the use of Card Match media could improve my ability to learn Japanese vocabulary. Keywords: Media, Card Match, Vocabulary of Objects (Meishi), Experimental ClassPenelitian ini mengkaji tentang penguasaan kosakata benda bahasa Jepang siswa kelas X MIA 4 SMA Negeri 17 Surabaya. Berdasarkan hasil wawancara pra penelitian dengan guru mata pelajaran bahasa Jepang, dalam proses pembelajaran di kelas dapat diketahui bahwa siswa masih mengalami kesulitan dalam menghafal serta memahami kosakata benda (meishi). Oleh karena itu, penggunaan media Card Match untuk mengatasi kesulitan siswa dalam menghafal serta memahami kosakata benda (meishi). Media Card Match merupakan media kartu yang setiap satu kosakata terdiri dari 3 kartu yang berisi hiragana, cara baca (yomikata) dan arti (imi). Cara memainkannya adalah yaitu dengan mencocokkan kartu yang berisi hiragana, cara baca (yomikata) dan arti (imi) kemudian ditempel dalam sebuah media. Penelitian ini bertujuan untuk mengetahui efektivitas media Card Match terhadap kemampuan penguasaan kosakata benda (meishi) dan respon siswa terhadap media Card Match dalam kemampuan penguasaan kosakata benda (meishi) pada kelas X MIA 4 SMA Negeri 17 Surabaya. Media Card Match telah divalidasikan ke ahli media. Penelitian ini merupakan penelitian eksperimen dengan menggunakan pendekatan kuantitatif dan termasuk dalam penelitian Quasi Experimental Design yang dilaksanakan pada tanggal 23-25 April 2018. Populasi dari penelitian ini adalah siswa kelas X MIA SMA Negeri 17 Surabaya dengan sampel kelas X MIA 4 sebagai kelas eksperimen sebanyak 34 siswa. Berdasarkan hasil lembar pre-test dan post-test kelas eksperimen diketahui bahwa media Card Match efektif digunakan atau mempunyai pengaruh positif pada kelas eksperimen. Hal tersebut dikarenakan media Card Match dapat memudahkan siswa dalam menguasai kosakata benda (meishi). Selain itu hasil dari perhitungan t-signifikansi, hasil yang didapat adalah 9,99. Nilai tersebut lebih besar daripada nilai t tabel yaitu 2,49. Sehingga disimpulkan bahwa media Card Match berpengaruh secara signifikan terhadap kemampuan penguasaan kosakata benda (meishi) siswa kelas X SMA Negeri 17 Surabaya tahun ajaran 2017/2018. Berdasarkan analisis data angket siswa yang menunjukkan kriteria kuat, sebanyak 93,38% mengatakan bahwa pembelajaran kosakata benda (meishi) dengan menggunakan media Card Match sangat menarik dan menyenangkan serta dapat menciptakan suasana pembelajaran yang aktif, sebanyak 88,97% mengatakan bahwa penggunaan media Card Match dapat meningkatkan motivasi belajar saya dalam mempelajari kosakata bahasa Jepang, sebanyak 91,17% mengatakan bahwa penggunaan media Card Match dapat memudahkan saya dalam mempelajari kosakata bahasa Jepang, sebanyak 90,44% mengatakan bahwa penggunaan media Card Match dapat melatih kerja sama dengan kelompok, sebanyak 93,38% mengatakan bahwa penggunaan media Card Match dapat meningkatkan kemampuan saya dalam mempelajari kosakata bahasa Jepang. Kata Kunci: Media, Card Match, Kosakata Benda (Meishi), Kelas Eksperimen